Riding the Energy Transition : Oil Beyond 2040 - Cherif, Reda (IMF Working Papers; Working Paper, 2017)
Recent technological developments and past technology transitions suggest that the world could be on the verge of a profound shift in transportation technology. The return of the electric car and its adoption, like that of the motor vehicle in place of horses in early 20th century, could cut oil consumption substantially in the coming decades. Our analysis suggests that oil as the main fuel for transportation could have a much shorter life span left than commonly assumed. In the fast adoption scenario, oil prices could converge to the level of coal prices, about USD 15 per barrel in 2015 prices by the early 2040s. In this possible future, oil could become the new coal.